Rainlily, Zephyranthes and Habranthus spp.: Low Maintenance Flowering Bulbs for Florida Gardens - Gary W. Knox (EDIS)
ENH1151, a 12-page illustrated fact sheet by Gary W. Knox, describes these small flowing bulbs that flower within a few days after a rainfall — where to plant them, how to care for them, how to propagate them, and common species and selections. Includes references. Published by the UF Department of Environmental Horticulture, November 2009.